INTERSEXUALITY, BODILY AUTONOMY, AND HUMAN RIGHTS: A LEGAL CRITIQUE OF EARLY CLINICAL INTERVENTIONS - dos Santos, Francimar Reis; Costa, Jussileida Feitosa Damasceno; da Costa Júnior, Francisco Teodoro; Furlan, Donizete Vaz; Porto, Lizandra Bruna da Silva (Editora Impacto Científico, 2025)
The scientific basis of this article has corollaries in several other branches of the social and human sciences. Intersex people are defined in medical science as human beings who do not fit into the typical definitions of male or female gender. The right to protection of these people, to their very existence, is a matter of absolute delicacy, closely related to other areas of life, such as ethics, sociology, anthropology, human rights and, above all, health as the greatest good. Several aspects of daily life, such as human rights, bodily autonomy, and early surgical interventions, were analyzed through the lens of intersexuality as a right. The interferences of Catholicism under the binary aspect were analyzed clearly and objectively, creating a kind of barrier to new concepts of gender contrary to the binary system preached for centuries by Catholic rules. Understanding and accepting non-binary people in the current social context as holders of fundamental rights is a crucial task for the realization of the fundamental right to life, happiness, and the self-control of one's own body and will, such as avoiding premature surgeries, which will be studied, beginning with the free disposition of the body in these cases. Ultimately, the study led to a view of non-acceptance of premature surgical interventions considered "normalization" of sex, since they are technically conceptualized as discriminatory practices that should be eliminated by the State as the entity protecting and guaranteeing public order norms that encompass an entire community. The intersex theme was worked on diligently, and the subject was analyzed in a way that accepts their medical condition, which affirms that such people live with a disorder of sexual development, an inalienable pathological condition for people with this diverse genetic makeup. Thus, the necessary study arose for an analysis of the theme of intersexuality in Brazilian law and its social implications.DOI: https://doi.org/10.56238/edimpacto2025.084-019